Self-acting optimal design of spindle speed variation for regenerative chatter suppression based on novel analysis of internal process energy behavior. (1st December 2020) - Yamato, Shuntaro; Ito, Takamichi; Matsuzaki, Hirohiko; Fujita, Jun; Kakinuma, Yasuhiro
Abstract: Spindle speed variation (SSV) is a well-known effective and flexible technique to suppress chatter vibration by disrupting regenerative effect. In most research, the SSV is properly designed by a large number of complex stability simulations including identification of machine dynamics with time consumption or costly experiments while varying design parameters; hence, this approach cannot be on-line or integrable in the machine tools for autonomous self-suppression of chatter vibration. This paper presents a programmable optimal design methodology for sinusoidal spindle speed variation (SSSV), which only requires measuring the chatter frequency and can incorporate the machine constraints into the design procedure. The design concept is based on the minimization of kinematic internal process energy balance during SSSV cycle for efficient chatter energy dissipation. For this purpose, the modulation index, which is originally defined for frequency modulation (FM) technology in radio communication engineering, is introduced into SSSV as a novel index. The novel design criteria in terms of SSSV frequency are also proposed for robust chatter suppression without a momentary destabilization during SSSV cycle, called as beat vibration. A series of time-domain SSSV simulation and boring tests are carried out in depth for verification. It can be concluded that, the parameter candidates suggested by the proposed design procedure can optimally dissipate the chatter with little beat vibration. Graphical abstract: Image 1 Highlights: Self-acting optimal design for SSSV by measuring chatter frequency is presented. Technological analogy between SSSV and FM in radio engineering is introduced. The modulation index (MI) is defined as a novel design index for SSSV process. The SSSV energy balance is described by the first-kind Bessel function with MI. The energy-based RVA selection and design criteria of RVF are newly proposed.